Akulturasi Islam dan Budaya Lokal dalam Tradisi Keagamaan Masyarakat Jawa - Anisa Dia Indrianah; Rieke Silvi Setya Ananda; Risha Shofwatul Mala; Linda Amiro Fitriani; Natasya Islami Hanifia Putri; Muhammad Fahreza; Nur Fadila; Anggun Puspita; Mochammad Fariq Ghaliby; M. Erfan Muktasim B (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The acculturation of Islam and local culture in Javanese society is a process of blending Islamic teachings and traditions that have developed over time without eliminating local cultural identity. This process occurs through the spread of Islam through a cultural approach, enabling society to accept Islamic teachings more openly. This study aims to examine the forms of acculturation of Islam and local culture in Javanese religious traditions and to understand the factors influencing this acculturation process. The study used a qualitative approach with a library research method. Data were obtained from various secondary sources, including scientific journals, books, academic articles, and previous research relevant to the theme of acculturation of Islam and local culture. Data collection was carried out through documentation, while data analysis used descriptive content analysis. The results of the study indicate that the acculturation of Islam and local culture occurs harmoniously in various aspects of community life, particularly in religious traditions such as Nyadran, selametan, tahlilan, and Sekaten. Acculturation is also evident in the arts and culture, such as wayang (wayang), gamelan, batik, and mosque architecture, which combine elements of Javanese culture with Islamic values. This process plays a role in strengthening the community's cultural identity and facilitating the spread of Islam without eliminating existing traditions. The implications of this research indicate that the acculturation of Islam and local culture is a crucial factor in shaping a harmonious, tolerant community, capable of maintaining a balance between religious values ​​and local cultural wisdom.